Triaxial strength and deformation characteristics and its constitutive model of high-strength concrete before and after high temperatures. (April 2021) - Zhen-jun, He; Yan-ni, Ma; Zhen-wei, Wang; Xiao-jie, Zhang; Xue-sheng, Zhang; Meng-jia, Ding; Chuan, Fu
Abstract: In this paper, the experiments were performed on the triaxial strength and deformation behavior for plain high-strength concrete (HSC) at different kinds of stress ratios ( α  =  σ 1 : σ 2 : σ 3  = 0.00: 0.00:-1, −0.10: −0.10: −1; −0.10: −0.27: −1 ;-0.10:-0.42:-1; −0.10:-0.52:-1; −0.10:-0.77:-1; −0.10: −1: −1), after the exposure to normal and high temperatures of 20, 200, 300, 400, 500 and 600 ℃, using a large static-dynamic true triaxial machine. The triaxial compressive strengths, peak strain and stress–strain curves were measured. The effects of the temperatures and stress ratios on the failure modes, strength and deformation of HSC were studied and analyzed, and the corresponding conclusions were given. The experimental results showed that the ratio of the triaxial to its uniaxial compressive strength depends on the stress ratios and temperature levels. An orthotropic constitutive model with temperature parameters for plain HSC under triaxial compression is established, which is in good agreement with the experimental results